PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN PPKN KELAS V SEKOLAH DASAR - Tirta Fitri Rahmawati (STKIP Subang, 2022)
The aim of this research is to develop an E-Module product based on Contextual Teaching and Learning in the material of Unity and Integrity for 5th grade of Elementary School. The development of this E-Module uses The Research and Development method with the ADDIE development model consisting of 5 stages including Analysis, Design, Development, Implementation, and Evaluation. The techniques of collecting data used in this research are interviews and questionnaires. The assessment of this research was carried out by involving three experts, an expert material lecturer, an expert media lecturer, and expert linguist lecturer and twenty three students of 5th grade at SDN Bendungan Hilir 05. Data analysis technique used in this research is descriptive statistical. The result indicate the E-Module based on Contextual Teaching and Learning for the material expert got a percentage of 88%, the media expert test got a percentage of 95%, and the linguist test got a percentage of 94%. The percentage of students trial for the one to one stage is 86%, small group is 88%, and field test is 91%. This E-Module based on Contextual Teaching and Learning is considered very feasible so, it can be used by student in learning for Civics on material of Unity and Integrity for 5th grade of Elementary School.